Demographic change and the German current account surplus - Matthias Schön (Deutsche Bundesbank, 2020)
This paper shows that demographic change plays an important role in the formation of a country's net foreign asset position. An ageing population both lowers the demand and increases the supply of capital in an economy. Fewer workers reduce the required capital stock. As a longer life span leads to a longer retirement phase individuals save more. Simultaneously, necessary adjustments of pay-as-you-go pension systems to an ageing society affect aggregate savings. Taking Germany as an example, this paper applies a two-region model with endogenous savings and labour supply that is augmented with demographic data projections for OECD countries. It shows that demographic change in Germany is an important determinant of the current account. Counterfactual pension reform simulations show that a fixed pension level increases the current account while a fixed pension contribution rate lowers it. An increase in the retirement age results in a strong negative effect on the current account as it reduces the capital supply and increases the capital demand in an economy.
Keywords: E27; E62; F21; H55; J11; 330; Demographic Change; Current Account; Pension System